ATB0, + transporter-mediated targeting delivery to human lung cancer cells via aspartate-modified docetaxel-loading stealth liposomes. (19th December 2016) - Luo, Qiuhua; Yang, Bin; Tao, Wenhui; Li, Jia; Kou, Longfa; Lian, He; Che, Xin; He, Zhonggui; Sun, Jin
Abstract : Tumor cells have an increased demand for amino acids to support their rapid growth and malignant metastasis. Abstract : Tumor cells have an increased demand for amino acids to support their rapid growth and malignant metastasis. Transfer of amino acids across plasma membranes depends on several amino acid transporters that are highly upregulated in tumor cells and are promising targets for tumor cell-selective therapy. In this study, stealth liposomal systems functionalized with aspartate-polyoxyethylene stearate conjugate (APS) were developed for transporter-mediated targeted delivery to ATB 0, +, which is overexpressed human lung cells. The resultant ATB 0, + -targeting liposomes (APS-Lips) consisted of a liposome core and the surface coverage of the APS modifier had an optimized density of 10%. APS-Lips had a uniform particle size distribution and high encapsulation efficiency of docetaxel (DTX, >80%). APS modification had a negligible effect on the DTX release from liposomes. Compared with Taxotere and unmodified liposomes, APS-Lips showed increased intracellular delivery and antitumor potency against human lung cells. Furthermore, competitive endocytosis studies showed that the cellular uptake of APS-Lips was notably decreased in the presence of glycine, a typical substrate of ATB 0, +, and was increased through adhesion to the cell membrane via transporter-substrate interactions. Finally, in vitro hemolysis and in vivo vascular irritation studies in rabbits confirmed the good blood compatibility and minimal vascular stimulation of the synthetic ATB 0, + -targeting material APS. These results demonstrated that the aspartate-modified liposomes could be a promising nanocarrier for ATB 0, + transporter-mediated targeted drug delivery to treat lung cancer.